(untitled) (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2024)
Based on the works of Alisher Navoi, this article talks about self- cultivation and ways to overcome it. In Navoi’s epics such as "Hayratul-Abror" and "Lison ut-Tayr", several verses about self-cultivation are analyzed.